ENGLISH-CANADIAN DRAMA OF THE POST-CONFEDERATION PERIOD: A TRADITION IDENTIFIED - JONES, HEATHER (My University, 1985)
English-Canadian drama of the post-Confederation period has suffered at the hands of criticism. The large amount of popular drama was ignored by criticism which sought "high art". Such criticism has served to dissociate twentieth century drama from its tradition. That this tradition is popular rather than esoteric makes this body of work more rather than less rewarding on close inspection. Three divisions based on form are noted: Literary, Nationalistic, and Popular drama. All three yield illuminating uses of language and form. Of especial interest is the development of social and domestic realism as a response to social changes, particularly to the militancy of women.
Keywords: English Language and Literature; English Language and Literature